From Forger to Author: William Henry Ireland's Shakespeare Papers - John Ridpath (Opticon1826, 2008)
It took over one hundred years for William Shakespeare to gain the literary pre-eminence familiar to contemporary readers. A renewed interest in the author’s work during the eighteenth century was marked by theatrical revivals, new editions of the plays and renowned Shakespearean performances by famed actor David Garrick. But with this resurgence in popularity, some readers began to call attention to perceived gaps in the bard’s biography. In the mid- 1790s, these gaps were briefly filled with ‘newly discovered’ letters, deeds and occasional poetry, exhibited to the public and finally published in 1796. Forged by William Henry Ireland, these documents refashioned Shakespeare to the tastes of his age. The forger went on to make larger creative impositions upon the life and work of the dramatist, writing himself into the playwright’s life and adapting his plays to meet eighteenth-century standards of decorum. And by the 1790s, literary forgery itself ‘bordered on a literary genre with its own kinds of rules and aspirations’. Enthralled by the notoriety of other literary forgers, Ireland created his own literature under a Shakespearean guise. Whilst his forgeries were quickly exposed, they ultimately served Ireland in establishing a literary identity of his own.
Keywords: forgery